Política de crédito e de comercialização e cooperativismo: estudo de caso de uma cooperativa da agricultura familiar de Bela Vista-GO - Rodrigues, Thiago Lopes (2023)
An agricultural family member has not always received special attention from the State. Historically, it has been relegated to the background and even threatened with extinction as a category. Recently, due to a change in the political scenario after the military dictatorship, it has become a source of studies, debates and a central character of public policies, in particular Pronaf, created in 1995. However, the reach of Pronaf continues to be a limiting factor to the rural development of family farming. Even having the right to access, the numbers join to a low adherence in the state of Goiás. Cooperatives, as spaces for socialization and mobilization, are seen as promoters in this process. In the wake of this thought, this research aimed to study and evaluate how cooperativism can act as a link between family members, recognized by law, and the public policies to which they are entitled. For this, the methodology used was the interview, with the application of a simulation with the members of a cooperative in the city of Bela Vista de Goiás, in addition to the literature review. Considering the aspects analyzed with the cooperative members, it was possible to identify the importance of public policies for local development. The results are strongly influenced by the influence of cooperativism on access to Pronaf. New studies must be introduced in order to substantiate this theory. The research was divided into Introduction, Hypothesis, Objectives, Literature Review, Methodology, Results and Discussion and Conclusion